Aplikasi Komik Interaktif Cerita Rakyat Jambi Berbasis Android - Muhammad Ismail (LPPM STIKOM Dinamika Bangsa, 2017)
The purpose of this research is to introduce folklore and tales which shaped Jambi’s culture today. As the world is getting more and more accustomed to more sophisticated and advanced technology, our children tend to forget cultural inheritance and prefer to spend their time on mobile phones. The research methodologies that are applied in this research are, in sequential order: Literature study, observation, application design, and acceptance test, which will ultimately yield an application to serve the purpose of this research. The new application will allow a more attractive delivery of folklores and legend of Jambi people via interactive comics with a unique drawing style. The application will also be one of the many medias to preserve the folklores as well as the history behind the lore itself.